2022
DOI: 10.1177/15248380221127255
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Harassment in Low- and Middle-Income Countries: A Qualitative Systematic Review

Abstract: Sexual harassment is a pervasive form of gender-based violence that has negative social and health impacts, yet there is only limited research available on sexual harassment in low- and middle-income countries (LMICs). The aim of this qualitative systematic review was to better understand how participants across a variety of countries and settings conceptualized sexual harassment and to investigate its causal factors, consequences, coping strategies, and recommendations for prevention and interventions. We sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…The search string used was the names of all LMICs as defined by the World Bank’s (2023) classification. This method has been used in evidence reviews with a contextual focus on LMICs (see, e.g., Hardt et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The search string used was the names of all LMICs as defined by the World Bank’s (2023) classification. This method has been used in evidence reviews with a contextual focus on LMICs (see, e.g., Hardt et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…This review highlighted the lack of a robust evidence base as prevalence ranged widely from 14.5% to 98.8%, and it was noted that due to the ambiguity of definition, it is difficult to measure among the studies ( Ranganathan et al, 2021 ). Research has also revealed that the consequences of sexual violence are serious and complex in LMICs ( Hardt et al, 2022 ). Importantly, Hardt et al’s (2022) study found that impacts vary across LMIC settings and are influenced by contextual and socio-cultural factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, harassing messages, sexual jokes, and inappropriate touching, even if not in intimate areas, constitute sexual harassment and are often not perceived as such. It is crucial to highlight the various forms of sexual aggression present in a hierarchical environment since they are often not obvious, leaving the aggressor in an advantageous position over the victim (21).…”
Section: Prevalence Of Harassmentmentioning
confidence: 99%
“…The patriarchal culture of Indonesia contributes greatly to the continuation of sexual harassment cases. Sexual harassment is made possible by the power disparities between men and women, which are maintained by rigid patriarchal norms and gender inequality (Hardt et al, 2022). In a patriarchal system, the male party believes that they are in a superior position and have full authority over women.…”
Section: How Socioculture Affected the Filmmentioning
confidence: 99%